Cutaneous manifestations of physical and sexual child abuse - Jennifer Noble; Earl Hartwig; Tor Shwayder (Wolters Kluwer Medknow Publications, 2020)
This article reviews cutaneous manifestations of physical and sexual abuse and a stepwise approach that dermatologists can apply to differentiate abusive from accidental injuries.